2020
DOI: 10.1038/s41598-020-62388-y
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Calprotectin As a Novel Biomarker For The Diagnosis of Pleural Effusion: a Multicentre Trial

Abstract: Discriminating between malignant pleural effusion (MPE) and benign pleural effusion (BPE) remains difficult. Thus, novel and efficient biomarkers are required for the diagnosis of pleural effusion (PE). The aim of this study was to validate calprotectin as a diagnostic biomarker of PE in clinical settings. A total of 425 patients were recruited, and the pleural fluid samples collected had BPE in 223 cases (53.7%) or MPE in 137 patients (33%). The samples were all analysed following the same previously validate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 24 publications
0
16
0
1
Order By: Relevance
“…In a cohort of 425 patients, pleural CLP levels ranged from 772.48 to 3163.8 ng/mL (median: 1939 ng/mL) in malignant PEs, and 3216–24,000 ng/mL in non-malignant PEs (median: 9209 ng/mL) [ 90 ]. For a cut-off value of ≤6233.2 ng/mL, a 96% sensitivity and 60% specificity were reported in discriminating malignant from non-malignant PEs [ 90 ], suggesting pleural CLP as a novel and useful diagnostic biomarker in patients with PE of uncertain etiology [ 90 , 92 ].…”
Section: Clp In Serous Effusionsmentioning
confidence: 99%
“…In a cohort of 425 patients, pleural CLP levels ranged from 772.48 to 3163.8 ng/mL (median: 1939 ng/mL) in malignant PEs, and 3216–24,000 ng/mL in non-malignant PEs (median: 9209 ng/mL) [ 90 ]. For a cut-off value of ≤6233.2 ng/mL, a 96% sensitivity and 60% specificity were reported in discriminating malignant from non-malignant PEs [ 90 ], suggesting pleural CLP as a novel and useful diagnostic biomarker in patients with PE of uncertain etiology [ 90 , 92 ].…”
Section: Clp In Serous Effusionsmentioning
confidence: 99%
“…It was finally found that calprotectin showed a considerably high diagnostic accuracy for MPE (AUC, 0.96). However, these results were not confirmed by three subsequent studies (41)(42)(43), which showed that the diagnostic accuracy (i.e., the AUC) of calprotectin in MPE was 0.68 (41), <0.50 (42), and 0.85 (43), respectively. This results inconsistency may be attributable to the wide disease spectrum in the different study cohorts, as well as to the use of different calprotectin assays.…”
Section: Calprotectinmentioning
confidence: 77%
“…However, these studies were limited, among other factors, by the small number of patients in which calprotectin was determined in our research laboratories. Thus, we carried out this multicentre study to validate calprotectin levels in PE as a diagnostic biomarker of malignancy in clinical settings [ 7 ]. In this study, calprotectin levels were measured using the conventional robotised equipment and employing the enzyme-linked immunosorbent assay (ELISA fCA ® , Bühlmann Laboratories) routinely used in our laboratory [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we carried out this multicentre study to validate calprotectin levels in PE as a diagnostic biomarker of malignancy in clinical settings [ 7 ]. In this study, calprotectin levels were measured using the conventional robotised equipment and employing the enzyme-linked immunosorbent assay (ELISA fCA ® , Bühlmann Laboratories) routinely used in our laboratory [ 7 , 8 ]. The results of this work were useful when making early clinical decisions about the treatment of these patients because the use of this marker can lead to better diagnoses and can help avoid possible adverse consequences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation